Anisotropic impedance surfaces activated by incident waveform - Homma Haruki; Akram Muhammad Rizwan; Fathnan Ashif Aminulloh; Lee Jiyeon; Christopoulos Christos; Wakatsuchi Hiroki (Nanophotonics, 2022)
Anisotropic impedance surfaces have been used to control surface wave propagation, which has benefited applications across a variety of fields including radio-frequency (RF) and optical devices, sensing, electromagnetic compatibility, wireless power transfer, and communications. However, the responses of these surfaces are fixed once they are fabricated. Although tunable impedance surfaces have been introduced by utilizing power-dependent nonlinear components, such a tuning mechanism is generally limited to specific applications. Here we propose an additional mechanism to achieve tunable anisotropic impedance surfaces by embedding transient circuits that are controllable via the type of incident waveform. By switching between the open and short states of the circuits, it is possible to separately control the unit-cell impedances in two orthogonal directions, thereby changing from an isotropic impedance surface to an anisotropic impedance surface. Our simulation results show that a short pulse strongly propagates for both x and y directions at 3 GHz. However, when the waveform changes to a continuous wave, the transmittance for x direction is reduced to 26%, although still the transmittance for y direction achieves 77%. Therefore, the proposed metasurfaces are capable of guiding a surface wave in a specific direction based on the incident waveform even with the same power level and at the same frequency. Our study paves new avenues regarding the use of surface wave control in applications ranging from wireless communications to sensing and cloaking devices.